2009
DOI: 10.1037/a0016412
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic events among undergraduate students: Prevalence and associated symptoms.

Abstract: This multisite study assessed the prevalence of exposure to traumatic events and associated symptoms among undergraduate students (N ϭ 1,528) using online surveys. Most students (85%) reported having experienced a traumatic event in their lifetime (Time 1) and 21% reported experiencing an event over a 2-month period during college (Time 2). The most common event reported at both time points was the unexpected death of a loved one. Lifetime exposures to family violence, unwanted sexual attention, and sexual ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
191
5
21

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(248 citation statements)
references
References 36 publications
20
191
5
21
Order By: Relevance
“…Briere and colleagues investigated the relationship between cumulative traumas of either interpersonal or non-interpersonal type and found that it was the exposure to multiple types of interpersonal trauma that was associated with the greatest risk for PTSD. In general, events where the perpetrator intentionally harms the victim, such as interpersonal violence, sexual abuse, torture, and terrorism, are more strongly related to health problems than non-intentional events such as accidents, natural disaster, and illness (Frazier et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Briere and colleagues investigated the relationship between cumulative traumas of either interpersonal or non-interpersonal type and found that it was the exposure to multiple types of interpersonal trauma that was associated with the greatest risk for PTSD. In general, events where the perpetrator intentionally harms the victim, such as interpersonal violence, sexual abuse, torture, and terrorism, are more strongly related to health problems than non-intentional events such as accidents, natural disaster, and illness (Frazier et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…31, nº 3 (octubre) with the findings of Bados et al (2008). Likewise, given the known association between TI and post-traumatic symptoms (Bovin et al, 2008;Humphreys et al, 2010;RochaRego et al, 2009) the importance of this type of event is congruent with the observation of current post-traumatic symptoms being greater when the earlier trauma involved physical violence in the family, sexual violence or childhood sexual abuse (Frazier et al, 2009;Owens & Chard, 2006;Vrana & Lauterbach, 1994).…”
Section: Discussionmentioning
confidence: 77%
“…It is worth noting, however, that in a study which used a measure similar to the TIS-BM, Volchan et al (2011) found an association between retrospective self-reports of TI during a traumatic event and restricted area of body sway when participants listened to a script of their traumatic experience. A third limitation of our study is that the results are based on the worst traumatic event experienced and this may not be representative of other events of the same type; for instance, the worst traffic accident a person experiences might not be representative of other motor vehicle accidents (Breslau et al, 1998;Frazier et al, 2009). Fourth, the fact that our data are correlational means that the predictors of TI we identified cannot be assumed to be its cause; indeed, there may be other variables that explain the relationship between the two, and current emotional distress may also influence the perception of past events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ως κορυφαία τραυματική εμπειρία κατηγοριοποιήθηκε οτιδήποτε μπορούσε να προσληφθεί ως ευθεία απειλή για τη ζωή του ατόμου. Τέλος, ιδιαίτερο ενδιαφέρον έχει το εύρημα ότι όσο περισσότερες τραυματικές εμπειρίες είχε βιώσει ένα άτομο, τόσο αυξάνονταν οι πιθανότητες να αναφέρει περισσότερα συμπτώματα μετατραυματικής διαταραχής άγχους (Frazier et al, 2009). Στην Ελλάδα το φαινόμενο της παιδικής κακοποίησης είναι επίσης συχνό.…”
Section: το ψυχικό τραύμαunclassified